Effect of Music Therapy on The Improvement of Clinical Symptoms and Cognitive Functions of Schizophrenia Patients Receiving Risperidone Therapy - Syamsuddin, Saidah; Pabilang, Mikael Sri (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Music therapy as a non-pharmacotherapy management has not been widely used. Data about effectiveness, ideal number of sessions and types/methods of music therapy have not been widely studied in Indonesia. Therefore, this study was designed to answer these problems so that music therapy can be applied appropriately. Objective : To determine the effect of music therapy on the improvement of clinical symptoms and cognitive function of schizophrenic patients that are receiving risperidone therapy. Methods : This study was an experimental study with comparative analysis. Sampling with consecutive sampling on the population of patients who were hospitalized in the Regional Special Hospital of South Sulawesi Province. The treatment group received risperidone therapy and music therapy (active and receptive) 6-8 sessions with a duration of 45 minutes/session, the control group only received risperidone 2-4 mg/day. The instruments used were the PANSS and the MoCA - Indonesian version, examined in the second and fourth weeks after music therapy. Results: There was a significant difference between the treatment group compared to the control group in decreasing the PANSS score for negative symptoms (p=0.000), general psychopathology (4th week p=0.011) and cognitive function (4th week p=0.000) especially on visuospatial components (p=0.001), attention (p=0.009) and abstraction (p=0.011). There was no significant difference between the treatment group compared to the control group in decreasing the PANSS score for positive symptoms (p=0.0.102) Conclusion: Music therapy can be a non-pharmacological therapy of choice to support the improvement of negative symptoms, cognitive function and general psychopathology in the stabilization phase of schizophrenic patients receiving risperidone.